Separatist and autonomous tendencies in modern Italy - Secler, Bartłomiej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article focuses on the autonomous and separatist pursuits that occur in present day Italy. The work was inspired by the consultative referendums of 2017 in the regions of Veneto and Lombardia. Their aim was to give the residents a chance to express their views regarding the possible expansion of the autonomy of these two administrative units. As a result of the plebiscites, a significant majority voted for the expansion of the autonomy, which might trigger the pursuit of more permissions for the regions.
Keywords: Italian Republic; autonomy; separatism; Italian regions; Lega Nord